2016
DOI: 10.1111/cea.12846
|View full text |Cite
|
Sign up to set email alerts
|

Community healthcare professionals overestimate the risk of fatal anaphylaxis for food allergic children

Abstract: In conclusion, we have found evidence that community pharmacists, school first aiders and primary care nurses in the UK systematically overestimate the risk of fatal anaphylaxis for a food allergic child. This overestimation may result in increased patient and carer anxiety. Community practitioners who manage childhood food allergy and anaphylaxis need to be educated about the level of risk for fatal anaphylaxis in such children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…Previous studies have suggested that children with food allergy and their mothers suffer increased anxiety and stress compared with other groups . We recently found that community healthcare professionals significantly overestimate the risk of fatal anaphylaxis for children with food allergy, which may contribute to feelings of anxiety . Allergic comorbidities such as asthma are often present in those with food allergy, and these can also be associated with anxiety in affected children and their caregivers .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have suggested that children with food allergy and their mothers suffer increased anxiety and stress compared with other groups . We recently found that community healthcare professionals significantly overestimate the risk of fatal anaphylaxis for children with food allergy, which may contribute to feelings of anxiety . Allergic comorbidities such as asthma are often present in those with food allergy, and these can also be associated with anxiety in affected children and their caregivers .…”
Section: Introductionmentioning
confidence: 95%
“…[4][5][6] We recently found that community healthcare professionals significantly overestimate the risk of fatal anaphylaxis for children with food allergy, which may contribute to feelings of anxiety. 7 Allergic comorbidities such as asthma are often present in those with food allergy, and these can also be associated with anxiety in affected children and their caregivers. 8,9 While oral and epicutaneous immunotherapy show promise as treatments to reduce immunologic sensitivity in people with food allergy, there is a need for treatments which effectively address the psychological and emotional burden of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals experiencing severe allergic reactions to food make up an important subgroup, and they experience considerable morbidity, and while fatal reactions are rare, they are also unpredictable. 72,73 Within the iFAAM project, a Food Allergy Severity Score (FASS) has been developed and validated. This has the potential to accurately describe previous allergic reactions at both a simple and more complex level.…”
Section: Summary and Con Clus I On Smentioning
confidence: 99%
“…They reported an apparent increase in fatal anaphylaxis rates, in contrast to recent UK and US findings—and highlighted upright posture as being associated with such cases, and a number of other risk factors specific to each trigger—for example most fatal food anaphylaxis occurred between the ages of 17 and 45 years. Although this journal has previously reported a low risk of fatal anaphylaxis for people with food allergy, Hanna et al showed community healthcare professionals overestimate this risk by approximately 1 log. This may have implications for the way we discuss risk with patients affected by food allergy.…”
Section: Clinical Allergymentioning
confidence: 87%